Business Resilience of Traditional Market During and After Facing Pandemic Covid-19 (Case Study of Cisalak Market) - Lokita Rizky Megawati; Siti Jahroh; Annisa Falimantik; Alfa Chasanah (School of Business, IPB University (SB-IPB), 2023)
Cisalak Market is one of the traditional markets in Depok City which operates for 24 hours every day. Technical Implementation Unit (abbreviated as UPT) as manager of the Cisalak Market has a vision of realizing its market as a center of economic growth in the orderly, clean, beautiful, and comfortable trade sector. Like the traditional markets in general, activities in Cisalak Market are still running normally and are still crowded with buyers. But since the outbreak of COVID-19, market activities have also been limited and caused a decrease in the number of visitors as well as in purchasing power. Community activities had also been quiet due to the massive spread of coronavirus or COVID-19. This situation will affect the performance of Cisalak Market, especially on the amount of income received by traders in the market. This research aims to analyze the resilience of the Cisalak Market business after facing the pandemic issue using a risk management approach. In particular, this study aims (1) to identify the risk and determine risk treatment of the Cisalak Market in the midst of this pandemic and (2) provide solutions that make it possible to be resilient in continuing a business during a post-pandemic period. This study will use fishbone analysis which will formulate the problem, search for the cause, and find the solution. Some respondents will be interviewed such as UPT of Cisalak Market as the market manager and traders in Cisalak Market. This study will find major problems and provide possible solution strategies Keywords: Cisalak Market, fishbone analysis, risk management, risk identification, risk treatment